2003
DOI: 10.1038/sj.npp.1300337
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Gene Expression in Post-Mortem Human Brain: Localization to Sex Chromosomes

Abstract: Gender differences in brain development and in the prevalence of neuropsychiatric disorders such as depression have been reported. Gender differences in human brain might be related to patterns of gene expression. Microarray technology is one useful method for investigation of gene expression in brain. We investigated gene expression, cell types, and regional expression patterns of differentially expressed sex chromosome genes in brain. We profiled gene expression in male and female dorsolateral prefrontal cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
151
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(162 citation statements)
references
References 32 publications
7
151
0
1
Order By: Relevance
“…Not surprisingly the genes with the largest magnitude difference in expression were X-and Y-chromosome linked, i.e. XIST (423 fold, p ≤10E-11) in the females, and RPS4Y in males (31.6 fold, p ≤2.0E-13), both of which have previously been reported as differentially expressed by gender in the mammalian brain (Eriksson et al, 1999;Vawter et al, 2004), and another Y linked gene DDX3Y which was overexpressed in males (111 fold, p ≤8.8E-15).…”
Section: Microarray Resultsmentioning
confidence: 99%
“…Not surprisingly the genes with the largest magnitude difference in expression were X-and Y-chromosome linked, i.e. XIST (423 fold, p ≤10E-11) in the females, and RPS4Y in males (31.6 fold, p ≤2.0E-13), both of which have previously been reported as differentially expressed by gender in the mammalian brain (Eriksson et al, 1999;Vawter et al, 2004), and another Y linked gene DDX3Y which was overexpressed in males (111 fold, p ≤8.8E-15).…”
Section: Microarray Resultsmentioning
confidence: 99%
“…This analysis was prompted by the recent observation that gender has a marked effect on gene expression in human dopaminergic SN neurons, influencing the patterns of gene expression in both normal brain and the response to PD (Cantuti-Castelvetri et al, 2007). Other microarray studies have also revealed gender differences in gene expression in normal human brain (Vawter et al, 2004), but there is little additional data available on the interaction of gender and disease state on neuronal gene expression in either humans or animal models. The importance of gender is emphasized by the fact that the incidence of PD is nearly twice that in men as in women (Baldereschi et al, 2000;Van Den Eeden et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…13,33 Microarray data analysis Cohort composition for microarray analysis-A control group analysis was conducted by splitting the controls into subgroups at a median pH of 6.87 and comparing the gene expression profile with PLMfit. This analysis was used to evaluate gene expression results for agonal-pH sensitive genes.…”
Section: Oligonucleotide Microarraysmentioning
confidence: 99%
“…13,33 Microarray data analysis Probe level model fit for condensation of affymetrix probe data-A robust probe level model (PLM) fits a linear model to Affymetrix microarray probe data and is freely available at http://www.bioconductor.org. A complete description of the PLM fit algorithm is available at http://www.stat.berkeley.edu/users/bolstad/Dissertation/Bolstad_2004_Dissertation.pdf.…”
Section: Oligonucleotide Microarraysmentioning
confidence: 99%